2020
DOI: 10.1247/csf.20010
|View full text |Cite
|
Sign up to set email alerts
|

Biliverdin Reductase-A Deficiency Brighten and Sensitize Biliverdin-binding Chromoproteins

Abstract: Tissue absorbance, light scattering, and autofluorescence are significantly lower in the nearinfrared (NIR) range than in the visible range. Because of these advantages, NIR fluorescent proteins (FPs) are in high demand for in vivo imaging. Nevertheless, application of NIR FPs such as iRFP is still limited due to their dimness in mammalian cells. In contrast to GFP and its variants, iRFP requires biliverdin (BV) as a chromophore. The dimness of iRFP is at least partly due to rapid reduction of BV by biliverdin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…The copyright holder for this preprint (which this version posted May 20, 2021. ; https://doi.org/10.1101/2021.05.19.444883 doi: bioRxiv preprint cells as reported previously (Kobachi et al, 2020), but did not show any change in iRFP fluorescence with BV or PCB treatment (Fig. S6B), probably because all iRFP molecules were occupied by BV.…”
Section: Pcb Can Be Used As a Chromophore In Mammalian Cellssupporting
confidence: 79%
See 1 more Smart Citation
“…The copyright holder for this preprint (which this version posted May 20, 2021. ; https://doi.org/10.1101/2021.05.19.444883 doi: bioRxiv preprint cells as reported previously (Kobachi et al, 2020), but did not show any change in iRFP fluorescence with BV or PCB treatment (Fig. S6B), probably because all iRFP molecules were occupied by BV.…”
Section: Pcb Can Be Used As a Chromophore In Mammalian Cellssupporting
confidence: 79%
“…The copyright holder for this preprint (which this version posted May 20, 2021. ; https://doi.org/10.1101/2021.05.19.444883 doi: bioRxiv preprint generate BV, and the knocked out of biliverdin reductase A (BVRA), which degrades BV to generate bilirubin, improves the brightness of iRFP through the additional accumulation of BV (Kobachi et al, 2020;Shemetov et al, 2017). On the other hand, because Caenorhabditis elegans can hardly produce BV (Ding et al, 2017), it is incapable of imaging iRFP by simply introducing only the iRFP gene in nematodes.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, it remains challenging to use NIR-GECO2 and NIR-GECO2G to image Ca 2+ dynamics with single-cell resolution in rodents where neuronal BV concentrations are low and cannot be substantially increased by the strategy of co-expressing HO1 [8]. A promising approach to overcome this challenge was recently described by Kobachi and colleagues, who demonstrated that knocking out the gene for BV reductase increases the BV concentration in mice and improves the brightness of NIR--GECO1 by 4.3-fold [22]. While the off-kinetics of NIR-GECOs are very similar to that of GCaMP6s or jGCaMP7s, the on-kinetics of NIR-GECO series are slower than that of GCaMP series.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the improved SynPCB systems could overcome the requirement of BVRA depletion for the PhyB-PIF optogenetics (Figure ), which could alleviate the concerns caused by toxicity through BVRA KO or KD. It has been reported that BVRA KO might cause modest abnormalities such as sensitization of oxidative stress. Meanwhile, all reports using BVRA KO mice indicate that BVRA deficiency does not affect the reproductive rate, weight, growth, and lifespans . We had not observed any detectable changes in proliferation rate in BVRA KO HeLa cells and BVRA KD mESCs .…”
Section: Resultsmentioning
confidence: 68%
“…53−55 Meanwhile, all reports using BVRA KO mice indicate that BVRA deficiency does not affect the reproductive rate, weight, growth, and lifespans. 56 We had not observed any detectable changes in proliferation rate in BVRA KO HeLa cells and BVRA KD mESCs. 35 On the basis of the evidence, BVRA depletion with RNAi or CRISPR/Cas9-mediated knockout is still the best way to readily utilize the PhyB-PIF system.…”
Section: ■ Results and Discussionmentioning
confidence: 99%